The Use of Brainstorming Strategy to Improve Students’ Speaking Ability - Hapri Octarina; Syamsul Rizal; Fera Zasrianita (Yayasan Karinosseff Muda Indonesia, 2021)
The purpose of this study to investigate whether brainstorming strategy can improve the students’ speaking ability. The subject of research was XI IPA 2 in Academic year 2020/2021. The design of this research is classroom action research (CAR). The researcher evaluates the students’ speaking in five forms those are, Pronunciation, grammar, vocabulary, fluency and comprehension. Before doing cycle 1 the researcher gave speaking test of pre-cycle, based on the result the test in pre-cycle; the researcher gave treatments of action 1 and action 2 they are planning, implementing, observing and reflecting to see improvement of students’ speaking ability after the treatments were given. The brainstorming strategy can improve the students’ speaking ability in two cycle. Then the researcher find out there is a significance difference between the mean score of students’ speaking ability in cycle 1 (62,24) and the mean score of students’ speaking ability in cycle 2 (75,68). There is impact of cycle 2 and the result can achieve the criteria of success. By comparing the means, the researcher concluded that improvement students’ speaking ability through brainstorming strategy is an effective to develop students’ speaking skill. Therefore, English teacher are encourage to teach speaking through brainstorming strategy.